Scratching increases epidermal neuronal branching and alters psychophysical testing responses in atopic dermatitis and brachioradial pruritus - Renkhold, Lina; Wiegmann, Henning; Pfleiderer, Bettina; Süer, Aysenur; Zeidler, Claudia; Pereira, Manuel P.; Schmelz, Martin; Ständer, Sonja; Agelopoulos, Konstantin (Frontiers in Molecular Neuroscience, 2023)
Background Chronic scratching imposes a major stress on the skin and can lead to itch intensity worsening, and consequently, patients may enter an itch–scratch cycle. This repetitive mechanical stress can result in lichenification, worsening of epidermal barrier function, and enhanced cutaneous inflammation. Furthermore, a reduction of intraepidermal nerve fibers was previously described in lichenification. Aim The aim of this study was to investigate the influence of chronic scratching on the epidermal neuroanatomy and on sensory changes, in particular the prevalence of hyperknesis and alloknesis in patients after mechanical, chemical, and electrical stimuli. Methods Analyses were performed on pruritic lichenified (chronically scratched), pruritic non-lichenified (not chronically scratched), and non-pruritic non-lesional (unaffected) skin areas of patients with inflammatory pruritus, i.e., atopic dermatitis (n = 35), and neuropathic pruritus, i.e., brachioradial pruritus (n = 34) vs. healthy matched controls (n = 64). Our fine-grained spatial skin characterization enabled specifically studying the differential effects of chronic scratching in inflammatory and neuropathic itch. Results Analysis of intraepidermal nerve fiber density showed rarefaction of fibers in all three skin areas of patients compared with healthy controls in both diagnoses. Even more, the two pruritic areas had significantly less nerve fibers than the unaffected skin, whereas electrically induced itch was massively increased. Epidermal branching of the remaining nerve fibers in lichenified/chronically scratched skin was increased, particularly in patients with brachioradial pruritus, which may contribute to the pronounced local neuronal sensitivity. Hyperknesis and alloknesis were found to increase independently of lichenification. Conclusion Our results indicate that chronic scratching may not affect intraepidermal nerve fiber density but leads to a stronger branching pattern of intraepidermal nerve fibers, which may contribute to local hypersensitivity. The increased sensitivity in the pruritic areas suggests mechanisms of peripheral sensitization, whereas the increased sensation of electrically and chemically induced itch in unaffected skin indicates central sensitization for itch.